Internet of Things : The New Government-to-Business Platform - World Bank Group (World Bank, Washington, DC, 2017)
The buzz around Internet of Things (IoT) has gathered momentum but the IoT phenomenon is poorly understood by governments and businesses. Governments are under pressure to become more innovative, evidence-based, and collaborative and IoT seems to offer opportunities such as increased competitiveness and innovation, and regulatory improvements that reduce the burden on business and increase compliance. In this report we examine the evidence on the ground to see how the theoretical potential of IoT implementation matches up with the reality on the ground and what can we learn from government agencies at the forefront of IoT implementation. The report draws on lessons from cities around the world (Germany, UK, Luxembourg, Estonia, Kazakhstan, Finland, Canada, USA, Japan, UAE, and India); it also provides a review of the IoT marketplace. The questions it answers include - what is IoT and why should governments care, how are different cities implementing IoT based solutions, and what are the main policy and other implications for government to fully utilize the potential of the technology while managing the associated risks and challenges? Findings include the fact that IoT implementation is still nascent in governments, the business models to scale pilots are still under-developed, the policy environment remains very patchy, and there is need to invest in digital capacity, data practices, and IoT infrastructure. The report includes a rough toolkit for government agencies.